The Relationship Between the Internalization of Religious Moderation Values and the Emotional Intelligence of Students at Buddhist Higher Education Institutions in Indonesia - Astri Chintya Astana; Tisya Permatasari; Susijati Susijati; Muninggar Rahma (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study aims to analyze the relationship between the internalization of religious moderation values and the emotional intelligence of students in Buddhist colleges in Indonesia. The values of religious moderation are measured through indicators of national commitment, tolerance, anti-violence, and acceptance of traditions. Meanwhile, emotional intelligence includes self-awareness, self-regulation, motivation, empathy, and social skills. The research employed a quantitative approach with a correlational design. Data were collected using questionnaires distributed to students and analyzed using statistical correlation tests. The results of the study indicate a significant relationship between the internalization of religious moderation values and the level of students' emotional intelligence. Students with a high internalization of religious moderation values tend to exhibit better emotional intelligence, particularly in the areas of empathy and self-regulation. These findings highlight the importance of integrating religious moderation values into higher education curricula to support the emotional and character development of students.